2014
DOI: 10.1111/jnc.12970
|View full text |Cite
|
Sign up to set email alerts
|

Localization of heat shock protein HSPA6 (HSP70B') to sites of transcription in cultured differentiated human neuronal cells following thermal stress

Abstract: Heat shock proteins (Hsps) are a set of highly conserved proteins that are involved in cellular repair and protective mechanisms. In order to identify potential stress-sensitive sites in differentiated SH-SY5Y human neuronal cells, localization of two inducible members of the HSPA (HSP70) family was investigated, namely HSPA6 (HSP70B') and HSPA1A (HSP70-1). Following heat shock, yellow fluorescent protein (YFP)-tagged HSPA6 and HSPA1A proteins localized to nuclear speckles that are enriched in RNA splicing fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 124 publications
(278 reference statements)
1
17
0
Order By: Relevance
“…Real-time PCR robustly detected high fold change HSPA6 mRNA levels. HSPA6 protein was widely detected by immunofluorescence in within smooth muscle cells, as has been reported for HSPA6 in colon cells, [17] neurons [18], and macrophages [19] .…”
Section: Resultssupporting
confidence: 67%
“…Real-time PCR robustly detected high fold change HSPA6 mRNA levels. HSPA6 protein was widely detected by immunofluorescence in within smooth muscle cells, as has been reported for HSPA6 in colon cells, [17] neurons [18], and macrophages [19] .…”
Section: Resultssupporting
confidence: 67%
“…Indeed, combined treatment resulted in augmented HSR, exemplified by up-regulation of heat-shock protein A6 (HSPA6) mRNA (Fig. 5G) encoding the heat-shock 70-kD protein (HSP70) family member HSP70B′, which localizes to the nucleolus upon heat shock (31).…”
Section: Fgf13 Depletion Augments Nucleolar Size and Increases Rrna Andmentioning
confidence: 99%
“…This change in the localization of stress proteins is interpreted as critically important for the regulation of transcription during the inception and after the stress or resumption of steady state (23). Another study has also shown that HSPs are localized in cytoplasm and nucleus of stressed as well as unstressed cells and change their localization upon stress (22).…”
Section: Discussionmentioning
confidence: 96%